Metode Pendidikan Islam Perspektif Al-Qur’an - Qowim, Agus Nur (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2020)
Education is a conscious effort that is held to explore and develop human capabilities so that a transformation occurs, both in terms of knowledge, behavior, or norms that have been set. Islamic education is different from other education because its size does not only look good or bad. Islamic education must be based on the Koran, which in Islam functions as the main source of law. In addition, Islamic education must also be based on the hadith. The final achievement is that humans have skills in aspects of education that are in harmony with these two main sources of law. So, the final goal is not just to change behavior, or thinking power, but everything must be in tune with the guidance of the Koran and Hadith. Educational and teaching activities can achieve success if supported by good components. Among the main components is the method. That is the way that must be taken by a teacher in educating his soul so as to achieve goals that are in line with the guidance of the Qur'an and Sunnah. The use of appropriate methods will largely determine the outcome of the education and teaching process. Thus, educators must be skilled at choosing and using methods to match the material and teaching material. Not to forget, as educators need to pay attention to several principles in the use of methods, so that teaching methods will lead to successful teaching.